Storage Quality of Some Sudanese Mango pulp Concentrates - Abdel-Rahman, Nawal A.; Ali, Dena O. M.; Ahmed, Abdel Halim R.; Mustafa, Muna M. (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2016)
This study was carried out to evaluate the effect of storage on the quality of concentrates of mango cultivars (called Dibsha, Galb Altour, Abu-Samaka, Kitchener and Shendi1). Mangoes pulp was concentrated at atmospheric pressure in open steam jacketed kettle. Preserved with potassium metabisulphate, stored at ambient temperature (30±5º C) and determine the appropriate shelf-life for these products. The concentrates appearance good physico-chemical properties: TSS%, pH, titratable acidity, reducing and total sugars. Moreover, best quality attributes to the organoleptic tests: colour, flavor, taste and overall quality; during 12 months storage.